PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA TANGRAM TERHADAP HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR KELAS V DI SEKOLAH DASAR - Agnes Trimulya; Deki Wibowo; Yoga Awalludin Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was conducted at SDN 1 Kuwu, Dempet District, Demak Regency, during the second semester of the 2025/2026 academic year. The problem addressed in this study was the low mathematics learning outcomes of fifth-grade students on the topic of the area of plane figures. This study aimed to determine the effect of implementing the Problem Based Learning (PBL) model assisted by Tangram media on students' learning outcomes. This research employed a quantitative approach using a Nonequivalent Control Group Design. The research subjects consisted of 54 students, including 26 students in the control class and 28 students in the experimental class. Data were collected through tests, interviews, and documentation. The data were analyzed using the normality test, homogeneity test, Independent Sample t-test, Paired Sample t-test, and N-Gain analysis. The results showed that the significance value of the Independent Sample t-test was 0.000 < 0.05, indicating a significant effect on students' mathematics learning outcomes. The N-Gain score of the experimental class was 72.4572, which was categorized as moderate, while the control class obtained 44.1087, which was categorized as low. These findings indicate that the implementation of the Problem Based Learning (PBL) model assisted by Tangram media had a significant and moderately effective impact on improving fifth-grade students' mathematics learning outcomes on the topic of the area of plane figures.